The Japanese occupation and the peculiarity of Philippine nationalism - Aguja, Hilton J. (2010)
Historical accounts of the Philippine experience with the Japanese occupation have inordinately emphasized the commission of war crimes and other despicable atrocities against the native population. This depiction may contain some kernel of truth, but it is not the entire story.

Japanese foray into Southeast Asia, though driven by its national interest and imperial designs for self-aggrandizement, has had the effect of decisively undermining European colonialism that had been entrenched in Southeast Asia for centuries. Most of the countries in Southeast Asia, with the exception of the Philippines, took a stimulus from the Japanese occupation to struggle for independence against their pre-war colonizers.

Consequently, efforts to reinstate pre-war colonial arrangements in Southeast Asia were confronted with emboldened independence movements across the area. The Japanese example of boldly standing up against the West became a source of encouragement. This by-product of Japanese colonialism, though undoubtedly not the intended effect, had significantly influenced nationalist movements in the area and reshaped the political landscape of Southeast Asia after the war.

Key Terms: Nationalism, Colonialism, Colonial Mentality, Treaty of Paris, Jones Law, Tydings-Mcduffie Law, Commonwealth Government, Greater East Asia Co- Prosperity Sphere.
Keywords: Philippines -- History -- 19th century -- Japanese occupation